2023
DOI: 10.1038/s41598-023-36879-7
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic abnormalities and genotoxicity induced by 2,4-dichlorophenoxyacetic acid during indirect somatic embryogenesis in Coffea

Abstract: Indirect somatic embryogenesis (ISE) is a morphogenetic pathway in which somatic cells form callus and, later, somatic embryos (SE). 2,4-dichlorophenoxyacetic acid (2,4-D) is a synthetic auxin that promotes the proliferation and dedifferentiation of somatic cells, inducing the ISE. However, 2,4-D can cause genetic, epigenetic, physiological and morphological disorders, preventing the regeneration and/or resulting abnormal somatic embryos (ASE). We aimed to evaluate the toxic 2,4-D effect during the Coffea arab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…In addition, the mechanism of natural accrued auxin on SE is related to the type of exogenous auxin, which added to the medium [27]. The effect of synthetic auxins on SE could be observed as NAA in Picea abies and P. omorika [28], 2,4-D (2,4-dichlorophenoxyacetic acid) in Coffea [29], and IBA in Digitalis lanata [30].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the mechanism of natural accrued auxin on SE is related to the type of exogenous auxin, which added to the medium [27]. The effect of synthetic auxins on SE could be observed as NAA in Picea abies and P. omorika [28], 2,4-D (2,4-dichlorophenoxyacetic acid) in Coffea [29], and IBA in Digitalis lanata [30].…”
Section: Introductionmentioning
confidence: 99%
“…These explants then cultured on MS medium containing 2,4-D 2 mg.L -1 for inducing somatic embryogenesis. The selection of 2,4-D as PGR for inducing somatic embryogenesis was based on consideration that 2,4-D is a powerful embryogenesis inducer and has succeeded in triggering explant response to embryogenesis (Caeiro et al 2022;Gustian et al 2022) although it was also reported can result in abnormalities related to epigenetic and genetic changes (Fraga et al 2016;de Morais Oliveira et al 2023). All of explants showed the mountain-like structure exactly at centre of former incision of SAM after 7-DAC (Figure 1B).…”
mentioning
confidence: 99%